Attrition and treatment outcomes among adolescents and youths living with HIV in the Thai National AIDS Program - Sirinya Teeraananchai; Thanyawee Puthanakit; Stephen J. Kerr; Suchada Chaivooth; Sasisopin Kiertiburanakul; Kulkanya Chokephaibulkit; Sorakij Bhakeecheep; Achara Teeraratkul; Matthew Law; Kiat Ruxrungtham (Elsevier, 2019)
Background: There are limited data describing the care outcome of youth living with HIV in Asia. We assessed attrition and treatment outcomes among youths with behaviourly acquired HIV (BIY) and adolescents with perinatally acquired HIV (PIY) who initiated antiretroviral treatment (ART) through the National AIDS Program (NAP) in Thailand. Methods: People living with HIV aged 10-24 years who initiated antiretroviral therapy (ART) from 2008 to 2013 through the Thai NAP and who were followed up until 2014 were included in the analysis. We assessed youths initiating ART: BIY aged 15-19 years (BIY1) and BIY aged 20-24 (BIY2) compared against PIY aged 10-14 years. Attrition rates (mortality and loss to follow-up [LTFU]) were calculated and potential associations were assessed using Cox regression. Logistic regression was used to assess associations with treatment failure. Results: Of 11,954 individuals, 9909 (83%) were BIY with a median follow-up of 2.1 years and 17% were PIY with 4.2 years of follow-up. The median baseline CD4 cell count in BIY was higher (190 vs 154 cells/mm3) compared to PIY. Mortality rates were not significantly different among PIY (2.5 per 100 person years [PY], BIY1 3.1/100 PY and BIY2 2.9/100 PY, P=0.46). Compared to PIY with a crude LTFU rate of 2.9/100 PY, LTFU was higher in BIY1 (13.9/100 PY) and BIY2 (9.5/100 PY), P<0.001 and P<0.001, respectively. At 1 year after initiating ART, 16% experienced virological failure (viral load above 1000 copies/mL). Combined treatment failure and LTFU rates at 1 year after ART were higher among BIY1 (45.0%) and BIY2 (34.4%) compared to PIY (29.9%), P<0.001 and 0.001, respectively. Conclusion: Youth with behaviourally acquired HIV aged 15-19 years had poorer retention rates than older BIY and PIY. Targeted interventions for youth are urgently needed to improve overall treatment outcomes.